Thermo‐Adaptive Block Copolymers: Thermo‐Adaptive Block Copolymer Structural Color Electronics (Adv. Funct. Mater. 11/2021). (10th March 2021) - Park, Tae Hyun; Eoh, Hongkyu; Jung, Youngdoo; Lee, Geon‐Woo; Lee, Chang Eun; Kang, Han Sol; Lee, Junseok; Kim, Kwang‐Bum; Ryu, Du Yeol; Yu, Seunggun; Park, Cheolmin
Abstract : In article number 2008548, Seunggun Yu, Cheolmin Park, and co‐workers demonstrate thermo‐adaptive flexible electronic devices, based on thin self‐assembled block copolymer photonic crystal films. The reversible structural color of the thermo‐responsive photonic crystal film facilitates the development of a sensing display as well as diagnostic thermal patches, making it a step forward in emerging thermotronics suitable for a variety of human‐interactive flexible photo‐electronics.